Does Maternal Mental Health and Maternal Stress Affect Preschoolers' Behavioral Symptoms? - María Pía Santelices; Matías Irarrázaval; Pamela Jervis; Cristian Brotfeld; Carla Cisterna; Ana María Gallardo (MDPI AG, 2021)
(1) Background: Maternal stress and depression are considered risk factors in children's socioemotional development, also showing high prevalence worldwide. (2) Method: Participants correspond to a longitudinal sample of 6335 mother/child pairs (18-72 months), who were surveyed in 2010 and then in 2012. The hypothesis was tested with SEM analysis, setting the child's internalized/externalized problems as dependent variable, maternal depression as independent variable, and stress as a partial mediator. (3) Results: Both depression during pregnancy and recent depression has not only a direct effect on the internalizing and externalizing symptomatology of the child, but also an indirect effect through parental stress. Significant direct and indirect relationships were found. (4) Conclusions: Maternal depression and the presence of parental stress can influence children's behavioral problems, both internalizing and externalizing.